Q-Switched Thulium-Doped Fiber Laser with Pure Titanium-Film-Based Saturable Absorber - Muhammad, Ahmad Razif; Zakaria, Rozalina; Ahmad, Muhammad Taufiq; Rahim, Hazli Rafis Abdul; Arof, Hamzah; Harun, Sulaiman Wadi (Taylor & Francis, 2019)
We demonstrate the generation of Q-switching pulse train in thulium-doped fiber laser (TDFL) cavity by employing titanium-based saturable absorber (Ti-SA). The Ti-SA was fabricated by depositing titanium particles molecules using electron beam evaporation on the surface of a polyvinyl alcohol (PVA) film. Subsequently, stable Q-switched pulses were obtained within the 1,552 nm pump power range from 272.1 to 467 mW, with repetition rate tuned from 21.8 to 39.1 kHz. At the maximum pump power, the TDFL showed that the pulse duration of 2.22 μs and the maximum pulse energy of 124 nJ. © 2019, © 2019 Taylor & Francis.